Assessing the value of modelling and simulation in health care: An example based on increasing access to stroke treatment. Issue 2 (1st February 2019) - Soorapanth, Sada; Young, Terry
Abstract: The use of modelling and simulation (M&S) to design, operate, and troubleshoot care delivery processes has not been the subject of economic evaluation, so we undertake such an analysis of a modelling exercise to design better delivery: in this case, stroke care. First, the financial impact is assessed, followed by a cost-effectiveness analysis in which the clinical impact is also assessed. Because it is not usually possible to obtain all the costs of modelling, probabilistic sensitivity and threshold analyses are used to explore the uncertainties in the absence of complete information. Threshold analysis is then applied to calculate the upper bound cost and the level of service improvement that would be needed for M&S to represent good value for money.